EFEKTIVITAS PENYELENGGARAAN PELAYANAN PUBLIK DI WILAYAH KALIMANTAN - Fahil, Said (Jurnal Borneo Administrator, 2006)
The basic functions of the state are improving well-being of and delivering services to the public. In the context of regional autonomy framework, such functions are becoming much more essential. Unfortunately, empirical evidences show that public service performance is still far from being satisfying. Using NPM (New Public Management) approach, this paper analyses the policy implementation on enhancing service effectiveness in some district/city government in Kalimantan region. The study designates that there is a couple of service dimension need to be refurbished, particularly procedure / mechanism aspect and institutional aspect.  Keywords: pelayanan publik, otonomi daerah, Kalimantan